Green Synthesis of Silver Nanoparticles with Snake Fruit Peel Extract: A Preliminary Study For Optimization of The Preparation Technique - Dewi K. A. Kusumahastuti; Margareta N. Cahyanti; November R. Aminu; Jumiyati (Jurnal Penelitian Pendidikan IPA, 2024)
In Indonesia, the pulp of snake fruit is consumed while the peel remains unused. In this context, the phytochemical content of snake fruit aqueous extract was used as a reducing and capping agent in the preparation of silver nanoparticles (AgNPs). According to the phytochemical screening, snake fruit peel containing alkaloids, flavonoids, tannins, saponins, and polyphenols was used to synthesize AgNPs. Therefore, this research aimed to optimize the synthesis of AgNPs using snake fruit peel extract (Salacca zalacca) in terms of synthesis time, temperature and phytochemical screening. AgNPs were successfully synthesized using a volume ratio of 2:15 (20 mL of 1.00 mM AgNO3 to 150 mL of snake fruit peel extract) in a sealed container in a dark room. Furthermore, characterization was carried out using a UV-Vis spectrum and Fourier Transform Infrared Spectroscopy (FTIR). The UV-Vis spectrum characterization in a solution incubated for 30 minutes at 30 °C with a concentration of 1.00 mM AgNO3 was differentiated at a wavelength of 410 nm with an absorbance of 2.361. According to the FTIR characterization, there was an increase in the intensity of the O – H functional groups in the AgNPs solution compared to snake fruit peel extract. The results showed that the synthesis of AgNPs from snake fruit peel extract was optimal at a concentration of 1.00 mM AgNO3 at 30 °C and 30 minutes of incubation.